Migration and urban poverty and inequality in China - Albert Park; Dewen Wang (Institute for the Study of Labor (IZA), 2010)
Using data from recent surveys of migrants and local residents in 10 cities in 2005, this paper examines how migration influences measurements of urban poverty and inequality in China, and also compares how other indicators of well-being differ for migrants and local residents. Contrary to previous studies that report that the income poverty rate of migrant households is 1.5 times that of local resident households, we find relatively small differences in the poverty rates of migrants and local residents. Although the hourly wages of migrants are much lower than those of local residents, migrant workers work longer hours and have lower dependency ratios and higher labor force participation rates. Including migrants increases somewhat measures of urban income inequality. Significant differences between migrants and local residents are found for non-income welfare indicators such as housing conditions and access to social insurance programs.
Keywords: J61; O15; 330; Migration; urban; poverty; inequality; social protection; China; Migranten; Städtische Armut; Einkommensverteilung; Disparitätsmaß; Soziale Sicherung; China